(untitled) (Research, Society and Development, 2020)
The research had as objectives formulate an institutional classification based on the number of nursing services at the health institutions and present the real periods in time to performing the inspection of nursing exercise by the Rio de Janeiro Regional Council of Nursing´s inspection officers. It´s a descriptive and quantitative study based on descriptive epidemiology and statistics. The site of study was the Inspection Department of Regional Council of Nursing; the numerical data collection and documental analysis have been realized from documents issued by officers of Regional Council between the years of 2017 and 2018. Results: after investigation and statistic treatment by bivaried statistics of 1321 documents, and dispersion graphics elaboration was possible classify the institutions by size, using the association with the number of nursing services (A3, A2, A1, B e C), and also the time needed for each health establishment´s inspection. Conclusion: the formulation of systematized and scientifically based parameters can support an assertive and solute inspection process and the management of Inspection Department, so as to generate quality and productivity indicators. The models proposed in the current study were developed in order to contribute the work processes improvement and optimization, and inspection services management´s progress.